Next-generation sequencing analyses of the emergence and maintenance of mutations in CTL epitopes in HIV controllers with differential viremia control - Diogo Gama Caetano; Fernanda Heloise Côrtes; Gonzalo Bello; Sylvia Lopes Maia Teixeira; Brenda Hoagland; Beatriz Grinsztejn; Valdilea Gonçalves Veloso; Monick Lindenmeyer Guimarães; Mariza Gonçalves Morgado (Retrovirology, 2018)
Abstract Background Despite the low level of viral replication in HIV controllers (HICs), studies have reported viral mutations related to escape from cytotoxic T-lymphocyte (CTL) response in HIV-1 plasma sequences. Thus, evaluating the dynamics of the emergence of CTL-escape mutants in HICs reservoirs is important for understanding viremia control. To analyze the HIV-1 mutational profile and dynamics of CTL-escape mutants in HICs, we selected 11 long-term non-progressor individuals and divided them into the following groups: (1) viremic controllers (VCs; n = 5) and (2) elite controllers (ECs; n = 6). For each individual, we used HIV-1 proviral DNA from PBMCs related to earliest (VE) and latest (VL) visits to obtain gag and nef sequences using the Illumina HiSeq system. The consensus of each mapped gene was used to assess viral divergence, and next-generation sequencing data were employed to identify SNPs and variations within and flanking CTL epitopes. Results Divergence analysis showed higher values for nef compared to gag among the HICs. EC and VC groups showed similar divergence rates for both genes. Analysis of the number of SNPs showed that VCs present more variability in both genes. Synonymous/non-synonymous mutation ratios were < 1 for gag among ECs and for nef among ECs and VCs, exhibiting a predominance of non-synonymous mutations. Such mutations were observed in regions encoding CTL-restricted epitopes in all individuals. All ECs presented non-synonymous mutations in CTL epitopes but generally at low frequency (< 1%); all VCs showed a high number of mutations, with significant frequency changes between VE and VL visits. A higher frequency of internal mutations was observed for gag epitopes, with significant changes across visits compared to Nef epitopes, indicating a pattern associated with differential genetic pressure. Conclusions The high genetic conservation of HIV-1 gag and nef among ECs indicates that the higher level of viremia control restricts the evolution of both genes. Although viral replication levels in HICs are low or undetectable, all individuals exhibited CTL epitope mutations in proviral gag and nef variants, indicating that potential CTL escape mutants are present in HIC reservoirs and that situations leading to a disequilibrium of the host-virus relationship can result in the spread of CTL-escape variants.